Definition durability process fermentation in manufacturing bioethanol - Ярощук, Людмила Дем’янівна; Раухвергер, Ірина Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2012)
Here is considered process of fermentation in manufacturing bioethanol. It is offered the algorithm of forecasting durability process. It is accomplished the exploration of the methods of forecasting. We can see some schemes of automatic control to stop the process without forecasting and computer control system of forecasting algorithm